PERCEPTION OF MUAMALAH JURISPRUDENCE ON PAYMENT METHODS IN ONLINE BUSINESS - Herlina (Al-Iqtishad: Jurnal Ekonomi Syariah, 2021)
Increasingly sophisticated technology brings online business transactions in all forms of human activity. This manual business change has both positive and negative impacts related to objects or malls. Muamalah fiqh directs business people and the community (especially those who are Muslim) to always adhere to the patterns and principles of Islamic sharia muamalah. This article uses research with a qualitative approach that examines phenomena that occur in society, using several reference journals, books and exposure to problems both on social media and in the relevant realities of life. This study resulted in findings about understanding (fiqh) in doing business online must always use the principles of muamalah and the principles of Islamic law. Online business is created to facilitate buying and selling transactions with the intention of helping each other and benefiting the interests of each other. The basis of these intentions and objectives must still adhere to vigilance in transactions because the goods are not seen by the buyer directly. There are 2 (two) payment systems in this online business, namely transfer and Cash On Delivery (COD). The research findings are more inclined to the COD system which is safer because the receipt of the goods (even though the consumer has not seen the purchased goods) will give a sense of security to the buyer and the seller has made transactions according to sharia with the concept of goods with money being given. The conclusion is that buyers are not recommended to make payment transactions other than COD in online businesses.